The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.10421
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of koumine from Gelsemium Elegans Benth. and its therapeutic effect on collagen-induced arthritis in mice

Abstract: This study aimed to investigate the therapeutic effect of koumine on collagen-induced arthritis (CIA) in mice. Koumine was extracted from Gelsemium Elegans Benth. The CIA model was established in Balb/c mice. Forty successfully modeled mice were randomly divided into model group and 2, 4 and 8 mg/kg koumine groups, 10 mice in each group. Another 10 normal mice were selected as control group. The 2, 4 and 8 mg/kg koumine groups were treated with 2, 4 and 8 mg/kg koumine, respectively, for three successive weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Such evidence was also demonstrated by an in vivo study in which koumine pre-treatment (4.0 and 8.0 mg/kg, p.o. , for 3 weeks) exhibited a therapeutic effect on CIA in mice through regulation of RORγt/Foxp3 signal pathway and modulation of Th17/Treg immune imbalance 63 .…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Such evidence was also demonstrated by an in vivo study in which koumine pre-treatment (4.0 and 8.0 mg/kg, p.o. , for 3 weeks) exhibited a therapeutic effect on CIA in mice through regulation of RORγt/Foxp3 signal pathway and modulation of Th17/Treg immune imbalance 63 .…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…In an anxiety model, koumine demonstrated significant anxiolytic effects at doses of 0.5 mg/kg and 1.5 mg/kg [15]. Therapeutic efficacy against collagen-induced arthritis (CIA) in mice was observed at Koumine doses of 2, 4, and 8 mg/kg [28]. In this study, zebrafish larvae in the 50, 75, and 100 mg/L groups showed obvious malformations such as a shortened body length, pericardial edema, yolk sac edema, and curved tails.…”
Section: Discussionmentioning
confidence: 99%